Bias Gender Dalam Masyarakat Muslim: Antara Ajaran Islam Dengan Tradisi Tempatan - Ramli, Mohd Anuar (Jurnal Fiqh, 2010)
The issue of gender bias into polemics among Muslim scholars. This scenario triggered by the view that blames the feminist epistemology of religious and traditional male dominated society patriarchy in Islam as a factor in the occurrence of gender bias against women. Therefore, this article will discuss how Islam came with the release of her policy, the supply of a number of rights and responsibilities appropriate to the existence of a caliph or a slave. In addition, there are several factors that cause gender injustice against women, whether internal in nature such as the interpretation of religious tradition or external, such as the community. Finally, a number of issues of gender bias that occurs in the Muslim community made to assess whether the practice is based on the resolution of the Qur?an and the Prophet SAW pattern by al-Sunnah, or traditions they are based on the community (Tribal Tradition).